Fotodegradasi Metilen Biru oleh Metal Organic Framework (MOF) Fe-PTC dengan Penambahan H2O2 dan Dioptimasi Menggunakan Desain Box Behnken - Fathurrahman, Muhammad; Zulys, Agustino; Gunlazuardi, Jarnuzi (Jurnal Kartika Kimia, 2023)
Metal-organic framework (MOF) is a group of materials that can act as a photocatalyst to degrade dyes under visible light. This research aims to synthesize a new MOF material using iron metal (Fe) and the organic linker perylene-3,4,9,10-tetracarboxylate (PTC) via the solvothermal method, then characterize it using FTIR, XRD, DRS, and SEM-EDS, as well as its application in photodegradation of methylene blue dye by MOF Fe-PTC with the addition of H2O2 using a Box Behnken design. FTIR spectrum with absorption at a wave number of 572 cm-1 which identifies the presence of bonds between Fe and O. Solubility tests show that the material was difficult to dissolve in polar, semipolar, and nonpolar solvents. EDS Mapping which shows the presence of the Fe element with a weight percentage of 21.6%. The synthesized MOF Fe-PTC has a degree of crystallinity of 46.56% and an average crystal size of 50.9 nm with the highest diffraction peak at 2θ = 33.16°. DRS analysis shows that the MOF Fe-PTC has a bandgap energy of 1.93 eV with a maximum wavelength (lmax) of 638 nm. Characterization using SEM shows that the MOF Fe-PTC has a shape like a cylindrical tube. The optimum conditions obtained from photodegradation of methylene blue by MOF Fe-PTC with the addition of H2O2 under visible light irradiation of 250 W statistically are 1.35 mg for photocatalyst weight, 0.22 M for H2O2concentration, and 135 minutes for contact time.